María Rosa Lojo, Amores insólitos de nuestra historia, Buenos Aires, Alfaguara, 2001. - Rodríguez, Raquel B. (2002)
Fil: Rodríguez, Raquel B.. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras